Oral White Lesions: An Updated Clinical Diagnostic Decision Tree - Hamed Mortazavi; Yaser Safi; Maryam Baharvand; Soudeh Jafari; Fahimeh Anbari; Somayeh Rahmani (MDPI AG, 2019)
Diagnosis of oral white lesions might be quite challenging. This review article aimed to introduce a decision tree for oral white lesions according to their clinical features. General search engines and specialized databases including PubMed, PubMed Central, EBSCO, Science Direct, Scopus, Embase, and authenticated textbooks were used to find relevant topics by means of MeSH keywords such as “mouth disease„, “oral keratosis„, “oral leukokeratosis„, and “oral leukoplakia„. Related English-language articles published since 2000 to 2017, including reviews, meta-analyses, and original papers (randomized or nonrandomized clinical trials; prospective or retrospective cohort studies), case reports, and case series about oral diseases were appraised. Upon compilation of data, oral white lesions were categorized into two major groups according to their nature of development: Congenital or acquired lesions and four subgroups: Lesions which can be scraped off or not and lesions with the special pattern or not. In total, more than 20 entities were organized in the form of a decision tree in order to help clinicians establish a logical diagnosis by a stepwise progression method.